Same, Same But Different? Cognitive Behavioural Treatment Approaches for Paediatric CFS/ME and Depression. Issue 4 (9th March 2017) - Loades, M.E.; Chalder, T.
Abstract : Background: Approximately one in three children and young people with chronic fatigue syndrome (CFS/ME) also have probable depression. Cognitive behaviour therapy (CBT) has a growing evidence base as an effective treatment approach for CFS/ME and for depression in this population.Aims : Given the high degree of co-morbidity, this discussion paper aims to compare and contrast CBT for CFS/ME and CBT for depression in children and young people.Method : The existing literature on CBT for depression and CBT for CFS/ME, in relation to children and young people was reviewed.Results : Whilst there are commonalities to both treatments, the cognitive behavioural model of CFS/ME maintenance includes different factors and has a different emphasis to the cognitive behavioural model of depression, resulting in different intervention targets and strategies in a different sequence.Conclusions : A collaborative, formulation-driven approach to intervention should inform the intervention targets and treatment strategies.